Design and Implementation of Web Crawler Based on C++ - Song, Zijin (Journal of Artificial Intelligence and Information, 2025)
With the booming development and continuous progress of the design and artificial intelligence industries, the demand for high-quality and diverse images is showing an explosive growth trend. This trend is not only reflected in creative design and product development, but also deeply rooted in multiple cutting-edge fields such as machine learning and computer vision. However, in the face of massive image resources, manually accessing websites and downloading images one by one appears time-consuming and laborious, greatly limiting work efficiency and the scale of data acquisition. Therefore, developing efficient and automated tools to collect images has become a top priority. In this context, this article elaborates on the design and implementation of a web crawler system based on the C++programming language. This web crawling system focuses on processing websites that use the HTTP protocol, and can efficiently penetrate webpage structures, accurately locate and extract image resources. Users only need to provide the URL of the target website as a starting point, and the crawler will automatically start working by parsing the webpage content, identifying and downloading all available image files. This process not only greatly reduces the manual burden, but also significantly improves the speed and breadth of image collection, providing a solid foundation for subsequent image processing, analysis, and model training. In addition, the design of the crawler system considers flexibility and scalability, making it easy to adjust and optimize according to specific needs to adapt to the constantly changing network environment and image acquisition requirements.